Papillary tumor of Pineal Region in a 5-year-old male child: A rare entity - Gupta, Kanika; Khursheed, Sumat; Nayil, Khursheed; Khursheed, Sumaira; Makhdoomi, Rumana (Asian Journal of Neurosurgery, 2021)
Papillary tumor of the pineal region (PTPR) is a rare grade II to III pineal lesion. These tumors mostly occur in adults, only rarely in children, with six cases in children under the age of 16 years (10.2%) up to now. We report the case of a 5-year-old male child presenting with worsening headaches, abnormally enlarged head since birth and visual disturbances. Imaging reveals a mass in the region of the pineal gland. The third and lateral ventricles were enlarged. The patient underwent a gross-total surgical resection of pineal mass through a suboccipital supracerebellar approach and tissue sent for histopathological examination and an available immunohistochemical workup has been done which confirmed the diagnosis of papillary tumor pineal region. This case highlights the histopathological features, imaging along clinical presentation similar to those in the original description of this rare entity PTPR. More studies are required to determine the prognosis and standard treatment protocol of this rare entity.
Keywords: Malignant tumor; papillary tumor of the pineal region; pineal gland